Accounting as a discipline for study and practice: 1986* - BELL, PHILIP W. (Contemporary Accounting Research, 1987)
The long search for accounting principles has tended historically to be practice ‐and standards‐oriented. It is the author's contention that accountants might do better to think of themselves first and foremost as being involved in an intellectual discipline. Concern should be with subject matter , the nature of theory employed to handle problems dealing with that subject matter , and the methodology to be employed in verifying that theory. What has been put forward as a revolution in accounting thought in recent years may in this context come out as something more evolutionary in nature. We have: (1) useful extensions in subject matter — Information Economics and Agency Theory in particular; and (2) a sometimes healthy emphasis on and sometimes unhealthy obsession with empiricism in both macro (security market) and micro (choice decision) research. In fact, concern with both positive and normative questions, and employment of both logic and empiricism in our thinking, are essential in the study and practice of our discipline. The best of new thinking would seem to be complementary with , rather than a substitute for the best of what has gone on before. Résumé. La longue quête de «principes comptables» a été orientée historiquement vers la pratique et les normes. De l'avis de l'auteur, les comptables feraient mieux de se considérer comme œuvrant tout d'abord au sein d'une discipline intellectuelle. L'intérêt devrait porter sur le sujet , la nature de la théorie utilisée afin de prendre en charge les problèmes reliés audit sujet , et la méthodologie à être utilisée dans la vérification de cette théorie. Ce qui a été avancé dans les dernières années comme une révolution de la pensée comptable pourrait donner lieu dans ce contexte à quelque chose d'une nature plus évolutionniste. Nous possédons (1) des prolongements utiles dans le sujet — particulièrement l'économique de l'information et la théorie mandant‐mandataire; et (2) parfois une saine importance et à l'occasion une obsession malsaine de l'empirisme, accordées à la fois aux recherches de type macro (marchés financiers) et micro (décisions et choix des individus). De fait, le souci pour à la fois des questions positives et normatives, et l'utilisation dans notre réflexion à la fois de logique et d'empirisme, sont essentiels à l'étude et à la pratique de notre discipline. Les meilleurs aspects de la nouvelle pensée devraient être un complément plutôt qu'un substitut aux meilleurs aspects de l'approche antérieure.